Noise exposure management system based on Factories and Machinery (noise exposure) Regulations 1989 - Leong, Weng Kai (2018)
Noise-induced Hearing Loss (NIHL) is high prevalence among the industries in Malaysia as NIHL is the highest case which accounted for 5366 cases received in 2015 among occupational diseases and poisoning. Too much noise exposure may cause a temporary change in hearing or a temporary ringing in workers’ ears which can contribute to noise-induced hearing loss. Also, excessive noise can also lead to poor verbal communication between workers and indirectly become a risk factor to cause an accident. Currently the noise regulations implementation degrees were varied from plant to plant due to lacking of systematic technique for companies and workers to comply with noise regulation which is Factories and Machinery (Noise Exposure) Regulation 1989 and maintain the effective safety programs. Due to these problems, a noise exposure management system needs to be developed in this study to overcome the issues. The objectives of this research are to develop framework of Noise Exposure Management System (NEMS), develop prototype of NEMS and validate the developed management system. The method used to develop NEMS is based on Plan-Do-Check-Act (PDCA) concept. “Plan” is adopted to study and understand the elements and requirements of Factories and Machinery (Noise Exposure) 1989. “Do” is adopted to develop framework and system. “Check” is adopted to validate the system by using real process plant data that collected. “Act” is adopted to optimize the system to make the system more efficient and fully comply with Factories and Machinery (Noise Exposure) 1989. The developed NEMS systematically guides the end users to identify gaps and solutions related to imperfection of the development, program and documentation of plant to comply with the noise regulations. With the implemented NEMS, companies and workers will able to comply with the regulation systematically.